Toxicity and bioaccumulation of manganese and chromium in different organs of common carp (Cyprinus carpio) fish. (2021) - Ali, Zeeshan; Yousafzai, Ali Muhammad; Sher, Nadia; Muhammad, Ijaz; Nayab, Gul E.; Aqeel, Syed Abdul Maajid; Shah, Syed Touheed; Aschner, Michael; Khan, Ijaz; Khan, Haroon
Graphical abstract: Highlights: Heavy metals effects fishes when its concentration arises from its normal. Bioaccumulation of manganese and chromium was studied in Cyprinus carpio on hematological and biochemical parameters. In organ, bioaccumulation is highest in the gills followed by intestine > muscles > skin > bones. It is concluded that heavy metal can readily bio accumulate in the organs of fish. Abstract: The present research work was carried out to determine the bioaccumulation of manganese and chromium in the gills, intestine, muscles, skin and bones, as well as its acute toxicity and effects on hematological and biochemical parameters in Common carp ( Cyprinus carpio ). Adult carps were exposed for 96 h to manganese sulphate and chromium chloride solution, a sub lethal concentration was used in the experiment. Bioaccumulation was highest in the gills followed by intestine > muscles > skin > bones. The concentration of hematocrit (HCT) (37.3 ± 0.36), hemoglobin (HGB) (9.0 ± 0.04), Red Blood Cells (RBCs) (3.7 ± 0.025), mean corpuscular volume (MCV) (121.2 ± 0.36), mean corpuscular hemoglobin (MCH) (41.3 ± 0.3) and mean corpuscular hemoglobin concentration (MCHC) (41.06 ± 0.072) was significantly higher at 96 h (P < 0.01) after exposure to manganese and chromium, while the concentration of platelets (PLT) (16.8 ± 0.12) and white blood cells (WBCs) (62.7 ± 0.11) was lower at 96 h of exposure. Serum glutamic pyruvic transaminase (SGPT) (40.6 ± 0.4), Blood Urea (13 ± 0.1), serum triglycerides (231.21 ± 0.04), high-density lipoprotein (HDL) (39 ± 0.07), serum Alkaline PO4 (242 ± 0.2), lactate dehydrogenase (LDH) (1239 ± 13.21), and serum Uric Acid (4.81 ± 0.33) were significantly higher (P < 0.01) at 96 h of exposure. The highest concentration of serum cholesterol (339 ± 0.09), serum reatinine (0.9 ± 0.01), low density lipid (240 ± 0.2) was observed at 24 h. Serum glutamic-oxaloacetic transaminase (SGOT) (19 ± 0.13), and serum albumin were at the highest level at 72 h (3.19 ± 0.07) (P < 0.01) post exposure.